Community forest management: Comparison of simulated production and financial returns from agarwood, tengkawang and rubber trees in West Kutai, Indonesia - ABUBAKAR M. LAHJIE; ISMINARTI ISMINARTI; B.D.A.S. SIMARANGKIR; R. KRISTININGRUM; YOSEP RUSLIM (Society for Indonesian Biodiversity, 2018)
Lahjie AM, Isminarti, Simarangkir BDAS, Kristiningrum, R, Ruslim Y. 2018. Community forest management: Comparison of simulated production and financial returns from agarwood, tengkawang and rubber trees in West Kutai, Indonesia. Biodiversitas 19: 126-133. Research was conducted in planted forests of agarwood (Aquilaria spp.) and tengkawang (Shorea macrophylla) and in plantations of natural rubber (Hevea brasiliensis) in West Kutai District, East Kalimantan Province, Indonesia. The research aimed (i) to find out the productivity of agarwood and tengkawang trees in mixed plantings (ii) to measure their rate of development in order to estimate the maximum Mean Annual Increment (MAI) for agarwood and tengkawang and (iii) to carry out a comparison with natural rubber production of the investment feasibility of planted forests of these trees using a financial analysis of Pay Back Period, Net Present Value (NPV), Net Benefit/ Cost (B/C) Ratio and Internal rate of Return (IRR). The research was based on measurements carried out in plots, 0.25 ha in extent, selected by systematic random sampling from three model plantations. Plantation Model I was a combination of agarwood and tengkawang in one piece of land in which the agarwood trees were planted at a spacing of of 5m x 2.5m and the tengkawang tree were also planted at a spacing of 5m x 2.5m. This means that there were a total of 200 agarwood saplings and 200 tengkawang saplings in the plot. Model II was the combination of agarwood and tengkawang in one piece of land, in which 167 agarwood saplings were planted and 166 tengkawang saplings were planted in a different planting arrangement (at the planting distance of 5m x 3 m). Model III was rubber trees in an area of 0.25 ha with 119 saplings. The data for natural rubber were collected in series from the farmers. The measurement variables for agarwood and tenkawang included the diameter and height of trees using series measurement until they reached 30 years and then the results were simulated. The research findings showed that in Model I, agarwood was found to have higher maximum MAI while in Model II, tengkawang was found to have higher maximum MAI. This was the result of a silvicultural technique in which thinning, maintenance and intermediate harvest were carefully controlled. These two models were feasible for business because the values of their IRR were 14% and 13.3% respectively, while in Model III, rubber cultivation was not feasible for business because the value of its IRR was only 4.7%.